Initial assessment on the use of cocoa pulp in complete feed formulation: in vitro dry matter and organic matter digestibility. (May 2018) - Natsir, A; Mujnisa, A; Mide, M Z; Purnomo, N; Saade, M F
Abstract: Cocoa pulp is a by-product from cocoa industry which is produced in large quantity, but very limited study has been carried out in utilizing it as energy source in animal feed. The purpose of this study was to assess the in vitro dry matter (IVDMD) and in vitro organic matter digestibility (IVOMD) of complete feed containing different levels of cocoa pulp. The experiment was carried out according to completely randomised design consisting of four treatments and three replications. The treatments were P0 = Complete feed containing 0% cocoa pulp, P1 = Complete feed containing 5% cocoa pulp, P2 = Complete feed containing 10% cocoa pulp, and P3 = Complete feed containing 15% cocoa pulp on dry matter basis. The results of the study indicated that the average IVDMD was 567, 538, 566, and 526 g kg -1 DM, while the average IVOMD was 522, 491, 502, and 461 g/kg DM, respectively for treatment P0, P1, P2, and P3. Statistical analysis indicated that increasing levels of coca pulp in the feed significantly affected (P<0.05) the IVDMD and IVOMD of the feed. In conclusion, cocoa pulp is potential to be used up to 10% in complete feed with corn cobs as the fibre source.